The Hungry Years : Confessions of a Food Addict - Leith, William (London Bloomsbury Publishing, 2005)
A story of food, fat and addiction that is both funny and heart-wrenching: it will change the way you look at food for ever.
Confessions of a Food Addict.
Keywords: Overweight persons -- Compulsive eaters -- Food--Psychological aspects